Analysis of the Potential of Gold Instalments as an Alternative Sharia Investment for UMKM in an Era of Global Economic Uncertainty - Vika Miftahul Jannah; Stevanus Antoni.R; Anne Monika Fristy (Islamic Circle, 2025)
This study analyzes the potential of gold installment schemes as a sharia-compliant investment alternative for micro, small, and medium enterprises in the context of global economic uncertainty. The background of the research highlights the need for UMKM to access safe, stable, and sharia-based investment instruments. The study aims to explain how gold installment schemes can function as an asset diversification mechanism and a tool for strengthening financial resilience. Using a descriptive qualitative approach, the methodology incorporates literature review, field observation, and interviews with UMKM actors and officers of sharia financial institutions. The findings indicate that gold installment schemes are viewed as accessible, affordable, and stable investment instruments that appeal to UMKM. Interview results reveal that such schemes support financial discipline while providing a sense of security in managing assets amid economic fluctuations. The discussion affirms consistency between the study’s findings and existing literature on gold as a safe haven asset while highlighting its relevance in the development of sharia investment products. The study concludes that gold installment schemes have strong potential to support UMKM financial resilience and should be enhanced through literacy programs, product innovation, and institutional reinforcement. This research contributes theoretical and practical insights to the advancement of Islamic economic studies.